All Days 2014
DOI: 10.2118/168650-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cement Sheath Durability: Increasing Cement Sheath Integrity to Reduce Gas Migration in the Marcellus Shale Play

Abstract: This study examines the effects of drilling, completion, and production operations and their associated cyclic stresses on a cement sheath. The operations performed after cement placement can damage cement sheath integrity and bond with the casing or formation resulting in loss of zonal isolation and sustained casing pressure often requiring remediation and reducing productivity. This paper describes evaluation of cement sheath failure resulting from cyclic stresses experienced while drilling, fracturing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Previous studies (McDaniel et al 2014) have reported PR values ranging from 0.23-0.32 for cements using a Class H base with various recipes. Reddy et al, (2007) presented dynamic PR values for foamed cements of different qualities (0-25%) that ranged between 0.17-0.23.…”
Section: Poisson's Ratiomentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies (McDaniel et al 2014) have reported PR values ranging from 0.23-0.32 for cements using a Class H base with various recipes. Reddy et al, (2007) presented dynamic PR values for foamed cements of different qualities (0-25%) that ranged between 0.17-0.23.…”
Section: Poisson's Ratiomentioning
confidence: 94%
“…This trend can be significant for design optimization due to the idea that an increase in PR can lead to a decrease in compressibility, which, in turn, allows the cement to play a better role in long term cement sheath integrity (Le Roy-DeLange, et al, 2000). McDaniel, et al (2014) reported YM values of Class H cements that varied between 5.2 GPa-11.3 GPa (7.54ϫ10 5 to 1.63ϫ10 6 psi). Reddy et al, (2007) presented dynamic YM values for foamed cements of different qualities (0-25%) that ranged between 12.41GPa-19.99 GPa (1.8ϫ10 6 to 2.90ϫ10 6 psi).…”
Section: Poisson's Ratiomentioning
confidence: 99%
“…To address potential issues and help operators make well-informed decisions regarding the long-term integrity of oil and gas wells, many companies, both in the service and operation sectors, have applied to some extent a more comprehensive approach when designing OWCs, taking advantage of the evolution of OWCs, both from the chemical (new systems) and engineering (new characterization tools) perspectives, to create an optimal sealant to help ensure integrity for the life of the well (Fig. In support of this statement, many studies report successful use of such techniques in yielding optimum long-term wellbore integrity in actual or simulated downhole environments (Krusche et al 2006;Shadravan et al 2014Shadravan et al , 2015aShadravan et al , 2015bGarnier et al 2007;De Andrade et al 2015;Godoy et al 2015;McDaniel et al 2014b;Griffith et al 2004;Jain et al 2014;Wang and Dahi Taleghani 2014b;Ramos et al 2009). Multiple datasets indicate significant variations in wellbore integrity (2.6 to 75%) over different time periods (Davies et al 2014).…”
Section: Impact Of Owc Evolution On Wellbore Construction Economics Amentioning
confidence: 99%
“…Industry is today capable of performing up to 60 stage frac jobs in unconventional wells. McDaniel and et al (2014) investigated cement sheath durability to reduce gas migration in the Marcellus shale. Most of the wells in that shale play, are not reaching the HPHT conditions but are all subject to stress loading during hydraulic fracturing.…”
Section: Hydraulic Fracturingmentioning
confidence: 99%